Organization of chicken DNA sequences homologous to the transforming gene of avian myeloblastosis virus. I. Restriction enzyme analysis of total DNA from normal and leukemic cells. - Perbal, B (1982)
Hybridization probes consisting of cloned DNA recombinants which represent different regions of the leukemogenic sequence (amv) from avian myeloblastosis virus were used to carry out a more detailed restriction endonuclease analysis of the homologous sequences (proto-amv) present in normal and leukemic chicken DNA. The results show that four large introns interrupt the normal cellular proto-amv sequences and that there is no major rearrangement of these sequences in leukemic myeloblasts.